Pain and Posttraumatic Stress Symptom Clusters: A Cross-Lagged Study - de Vries, Vivian; de Jong, Alette E. E.; Hofland, Helma W. C.; Van Loey, Nancy E. (Frontiers in Psychology, 2021)
Pain and posttraumatic stress disorder (PTSD) frequently co-occur but underlying mechanisms are not clear. This study aimed to test the development and maintenance of pain and PTSD symptom clusters, i.e., intrusions, avoidance and hyperarousal. The longitudinal study included 216 adults with burns. PTSD symptom clusters, indexed by the Impact of Event Scale-Revised (IES-R), and pain, using a graphic numerical rating scale (GNRS), were measured during hospitalization, 3 and 6 months post burn. Cross-lagged panel analysis was used to test the relationships between pain and PTSD symptom clusters. Cross-lagged results showed that in-hospital intrusions predicted pain and avoidance 3 months post burn. In-hospital pain predicted intrusions and avoidance 3 months post burn and a trend was found for hyperarousal (90% CI). In the second wave, intrusions predicted pain and hyperarousal. Pain predicted hyperarousal. This study provides support for an entangled relationship between pain and PTSD symptoms, and particularly subscribes the role of intrusions in this bidirectional relationship. To a lesser extent, hyperarousal was unidirectionally related to pain. These results may subscribe the driving role of PTSD, particularly intrusions, which partly supports the Perpetual Avoidance Model.